1994
DOI: 10.1128/jb.176.20.6270-6280.1994
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequence analysis of polyketide synthase genes from the daunomycin-producing Streptomyces sp. strain C5

Abstract: (23,25). Only in the cases of the tetracenomycin (40) and actinorhodin (5,19,34,55) PKSs, however, have biochemical characterizations also been carried out. Thus, most of the information on type II PKSs is derived from the strong conservation of gene structure among the PKS genes (23,25) and cross-functionality of the components (5,26,34,41). We describe here the structure of a gene region from Streptomyces sp. strain C5 that putatively encodes daunomycin biosynthesis and show that it has a significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
77
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 46 publications
2
77
0
Order By: Relevance
“…In genetic studies on anthracycline biosynthesis, similar small ORFs were identified in the biosynthetic gene clusters just upstream from the KS gene in S. peucetius (6), Streptomyces sp. strain C5 (20), Streptomyces nogalater (21), and S. galilaeus (4). Their homology with tcmH suggested that the encoded enzyme might catalyze the oxygenation of aklanonic acid anthrone to form aklanonic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In genetic studies on anthracycline biosynthesis, similar small ORFs were identified in the biosynthetic gene clusters just upstream from the KS gene in S. peucetius (6), Streptomyces sp. strain C5 (20), Streptomyces nogalater (21), and S. galilaeus (4). Their homology with tcmH suggested that the encoded enzyme might catalyze the oxygenation of aklanonic acid anthrone to form aklanonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Such genes are not found in typical type II PKS gene clusters like that of actinorhodin (2). However, similar small ORFs exist in known anthracycline biosynthetic gene clusters such as dauG/dnrG in the daunorubicin/doxorubicin biosynthetic gene cluster (6,20), and snoaB in the nogalamycin biosynthesis gene cluster (21) (Fig. 2).…”
mentioning
confidence: 99%
“…Biosynthesis starts with the polyketide pathway, where the carbon chain is built up by repeated Claisen condensations from acyl and malonate carbonyl units by the large polyketide synthase complex (8). These condensation steps are followed by a final cyclization to give the aglycone polyketide skeleton (9). The cyclized product is then further modified by a series of tailoring enzymes leading to, for example, glycosylation, hydroxylation, methylester hydrolysis, and decarboxylation (10 -15).…”
mentioning
confidence: 99%
“…1) are clinically important anthracycline chemotherapeutic agents (2, 11, 17), which are synthesized by a type II polyketide synthase (23,(42)(43)(44). The aglycone is formed by condensing nine extender units derived from malonyl coenzyme A onto a propionyl moiety to make a C 21 polyketide intermediate (21,23,(42)(43)(44)(45)50), which is reduced at C-9 from the carboxy terminus (43, 44), cyclized, and aromatized to form aklanonic acid (18,19,23,40,(42)(43)(44). Aklanonic acid is converted in four steps to ε-rhodomycinone (3,7,15,16,30,40,42,44), an intermediate that is accumulated in large quantities by most daunorubicin-producing strains (27,42,44,46).…”
mentioning
confidence: 99%